2022
DOI: 10.3390/jpm13010081
|View full text |Cite
|
Sign up to set email alerts
|

Is Cemented Dual-Mobility Cup a Reliable Option in Primary and Revision Total Hip Arthroplasty: A Systematic Review

Abstract: Background: Instability is a common complication following total hip arthroplasty (THA). The dual mobility cup (DMC) allows a reduction in the dislocation rate. The goal of this systematic review was to clarify the different uses and outcomes according to the indications of the cemented DMC (C-DMC). Methods: A systematic review was performed using the keywords “Cemented Dual Mobility Cup” or “Cemented Tripolar Cup” without a publication year limit. Of the 465 studies identified, only 56 were eligible for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This modular design allows for flexibility in addressing various patient anatomies and optimizing stability. Monoblock (non-modular) DM designs integrate the articulating surface with the acetabular shell, providing an alternative approach[ 6 , 8 ].…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…This modular design allows for flexibility in addressing various patient anatomies and optimizing stability. Monoblock (non-modular) DM designs integrate the articulating surface with the acetabular shell, providing an alternative approach[ 6 , 8 ].…”
Section: Surgerymentioning
confidence: 99%
“…Cemented DM implants, for instance, are utilized in both primary and revision surgeries. A systematic review by Ciolli et al [ 8 ] concluded that cemented DM cups represent an effective treatment option with favorable clinical outcomes[ 8 ].…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations